2018
DOI: 10.1245/s10434-018-6682-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast Conservation and Negative Margins in Invasive Lobular Carcinoma: The Impact of Oncoplastic Surgery and Shave Margins in 358 Patients

Abstract: Surgeons should consider routine use of oncoplastic techniques and shave margins when performing breast-conservation surgery for women with ILC as these methods are associated with significantly lower odds of having positive margins and higher breast-conservation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The clinical and radiologic features of this type of lesion can explain this result. We know this from the literature, confirmed also by our case studies 18,19…”
Section: Discussionsupporting
confidence: 84%
“…The clinical and radiologic features of this type of lesion can explain this result. We know this from the literature, confirmed also by our case studies 18,19…”
Section: Discussionsupporting
confidence: 84%
“…Although no long-term differences in recurrence rates and survival between BCS and OPS have been reported 13,19,22,[43][44][45] , current evidence regarding the impact of OPS on the re-excision rate is limited because the data are from single-centre studies with relatively few patients undergoing OPS (ranging from 31 to 1177), and in most studies the methodology was weak 11,13,44,[46][47][48] . The present results are in line with a meta-analysis 19 from 2018 that found a significantly lower risk of re-excision in patients who underwent OPS compared with those who had BCS (relative risk 0⋅66, 95 per cent c.i.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns that re-excision lumpectomy will fail to clear the margin can result in increased mastectomies, and in several series, women with ILC who have positive or close margins are significantly more likely to undergo completion mastectomy than women with IDC. 2,1215 While many investigators have reported on high positive margin rates in ILC, to our knowledge there are scarce data reporting the success rates of re-excision lumpectomy at clearing the initially positive margin. Understanding the likelihood of success is critical for patients to make informed decisions about whether to continue to pursue breast conservation after an initial positive margin, versus undergoing completion mastectomy.…”
Section: Introductionmentioning
confidence: 99%